2013
DOI: 10.1371/journal.pone.0062547
|View full text |Cite
|
Sign up to set email alerts
|

p63 Attenuates Epithelial to Mesenchymal Potential in an Experimental Prostate Cell Model

Abstract: The transcription factor p63 is central for epithelial homeostasis and development. In our model of epithelial to mesenchymal transition (EMT) in human prostate cells, p63 was one of the most down-regulated transcription factors during EMT. We therefore investigated the role of p63 in EMT. Over-expression of the predominant epithelial isoform ΔNp63α in mesenchymal type cells of the model led to gain of several epithelial characteristics without resulting in a complete mesenchymal to epithelial transition (MET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
4
33
0
Order By: Relevance
“…Repression of p63, a transcription factor required for maintenance of epithelial cell differentiation, induces EMT. [18][19][20] Morphologically, LG-SCP areas in our ccRCC cases appeared to derive directly from 'conventional' clear cell elements. There was a continual spectrum of gradually elongated clear cells to fully developed slender spindle cells with low-grade nuclei.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Repression of p63, a transcription factor required for maintenance of epithelial cell differentiation, induces EMT. [18][19][20] Morphologically, LG-SCP areas in our ccRCC cases appeared to derive directly from 'conventional' clear cell elements. There was a continual spectrum of gradually elongated clear cells to fully developed slender spindle cells with low-grade nuclei.…”
Section: Discussionmentioning
confidence: 62%
“…Claudins are suggested to be integral membrane proteins, responsible for maintaining epithelial cell polarity. Repression of p63, a transcription factor required for maintenance of epithelial cell differentiation, induces EMT …”
Section: Discussionmentioning
confidence: 99%
“…It was found that the effects of p63 on EMT markers are mediated mainly through miR-205 and p53 mutations [118], because mutant p53 can suppress the actions of p63. It has been reported that p63 is highly down-regulated when epithelial EP156T cells underwent EMT to become EPT1 cells [119] and over-expression of ΔNp63 in mesenchymal type cells led to gain of several epithelial characteristics [120, 121]. …”
Section: Transcription Factors Driving Emt In Pcamentioning
confidence: 99%
“…Genomic regions with potential functional impact were obtained from two major sources: annotated databases from UCSC table browser and published ChIP-Seq data from any prostate-derived cell lines or prostate tissue samples before available May 2014 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. These genomic regions were grouped into three categories: 1) coding regions defined by UCSC, including exons defined by the Consensus Coding Sequence (CCDS) project and coding regions for small nuclear RNA (snoRNA)/ micro RNA (miRNA) defined by miRBase and snoR-NABase, 2) regulatory elements defined by UCSC, including CpG island, ORegAnno, polyaDb, switchDbTss, targetscans and Vistaenhancers, and 3) binding regions defined by ChIP-Seq, including those for transcription factors (TFs), histone modifications (HMs), DNase I hypersensitivity (DHSs) and RNA Polymerase IIA (POLR2A).…”
Section: Genomic Regions With Potential Functional Impactmentioning
confidence: 99%
“…Recently, 23 additional PCa risk-associated SNPs were discovered by evaluating more than 10 million SNPs across the genome among 43,303 PCa cases and 43,737 controls from the international PRACTICAL Consortium [20]. In the meantime, more functionally annotated genomic regions have been identified by various ChIP-Seq analyses in prostate cell lines and tissues such as LNCaP, VCaP, RWPE1, 22Rv1, and PC3 [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. These additional pieces of information improve our ability to understand the location of PCa risk SNPs in relationship with functionally annotated regions in the genome.…”
Section: Introductionmentioning
confidence: 99%